ANALISIS KEBIJAKAN PERUSAHAAN “TEMPO MEDIA GROUP” DALAM MENGHADAPI ERA KEMAJUAN TEKNOLOGI INFORMASI DAN KONVERGENSI MEDIA - Maulina, Putri (Jurnal Public Policy, 2018)
The development of information and communication technology is currently endemic to almost every line of people's lives. One of the effects of technological progress is a massive change in the management of mass media companies. The mass media company must be able to increase its capacity in accordance with the technological advances, one of which is by utilizing the presence of other media that have different platforms in a media company management. The use of many media platforms is done by integrating a manual management system into various management systems based on modern technology. Integrating manual systems into various modern systems, in mass media companies is referred to as the process of media convergence. Tempo Media is a large print media company that has also integrated its management system into various types of media platforms. The system change in the Tempo media management certainly had an impact on the changes in policies in carrying out the company.Keyword : Policy, Technology, Media Convergence, Tempo Media